INFLUENCE OF SOME ORGANIC FERTILIZERS ON DATE PALM CV. BARHI - & Abood, Taha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This experiment was carried out at a private palm farm located in Great Musayib enacted / Babylon province on Barhi dates palm trees Phoenix dactylifera L. cultivar to determine the effect of spraying of chitosan and addition of both organic fertilizers and amino acids and seaweed extract in some vegetative traits (number of leaves, the circumference of the trunk and offshoots number) and leaves content (chlorophyll , dry weight and Proline) by spraying the chitosan at concentrations of 5 ml. l-1 and 10 ml.L -1 and the addition of both organic fertilizer and amino acids and seaweed extract at concentrations (1, 2) kg.tree -1 and (3 , 6) ml . L - 1 and (4, 8) ml l -1 respectively. Each treatment replicated five times with a factorial experiment using RCBD, one date palm for each experimental unit.The following are the main findings, The effect of chitosan spraying significantly increase the vegetative properties of the offshoots , the concentration 5 ml.l-1significant increases the number of weakness, trunk circumference and offshoots number, with 13.3 tinea, 31.9 cm, 3.09 offshoot sequentially. Spray 8ml.L-1(S2)of seaweed extract was significantly superior than control treatment and gave leaf chlorophyll content of 31.88 mg.g-1, leaf dry weight of 48.90 %. While the lowest results were in the control treatment, except the leaves proline content.